Caracterização e evolução aromática de espumantes moscatéis de Farroupilha (RS) durante o armazenamento e influência das leveduras nos vinhos moscatos - Marcon, Ângela Rossi (My University, 2018)
Farroupilha, located in the Serra Gaúcha region, is the county that owns the third largest production of grapes for processing in Brazil and the largest producer of muscat grapes, representing almost a half part of Brazilian production. In the last ten years, the production and commercialization of sparkling wines muscat in Brazil increased significantly, demonstrating a growing annual consumption. This product pleases the palate of the Brazilian and also of consumers from other countries, because every year sparkling Brazilian muscat win several medals in international competitions. Another important aspect was the achievement in 2015, of the Geographical Indication of Origin of wines from Farroupilha, contributing even more to the highlight of these products in the Brazilian and abroad market. Among the main varieties cultivated and used for the elaboration of quiet wines and sparkling wine muscat are Moscato Branco, Moscato Giallo, Moscato R2 and Malvasia de Candia. The more detailed knowledge of the sensorial, aromatic and qualitative characteristics of these products are important as they allow to characterize the profile of the wines and sparkling wines of this region. Therefore, the objective of this work was to determine the aromatic composition of the sparkling Farroupilha muscat; their evolution during storage; characterize wines elaborated with moscato varieties and determine the influence of yeasts Saccharomyces cerevisiae and Torulaspora delbrueckii on the chemical and sensorial composition of Moscato Branco wines. Physicochemical, chromatographic and sensorial analyzes were performed. The results allow to attribute to the sparkling wines with less time of storage citrus and fruity aromas and to the sparkling ones with more time, notes of apple, truffles, almonds, roses and honey. Each grape variety provides different aromas for each sparkling wines, contributing to a higher aromatic complexity. The Moscato Giallo variety attributes to the wine aromas that refer to fruits such as pear and pitanga, and herbs such as rosemary. The wines of the variety Moscato R2 stood out for the notes of citrus fruits and rosemary, and the wines of the variety Moscato Branco presented citric notes, pear and pitanga. The yeasts used also influenced the aromatic composition. The wines elaborated with pure yeasts of T. delbrueckii presented higher levels of isoamyl acetate (banana), ethyl hexanoate (fruits, anise), 2-methyl-1-propanol (alcoholic) and 2-phenylethanol (roses). These concentrations tend to decrease in mixed fermentations. Wines produced with S. cerevisiae 100% EC 1118 showed the highest levels of ethanal (green apple), 1-propanol (pungent), ethyl octanoate (pineapple, pear) and linalool (roses). Thus, this study demonstrates that, although the consuption tendency of muscat wine and muscat sparkling wine being between 12 and 18 months, these products have the potential to be consumed with greater storage time, without losing their typical characteristics. It was also verified that the sparkling wines of Farroupilha presented similar quality to the sparkling wine produced in the region of Asti, region of Denomination of Origin traditionally known with almost one hundred years of wine history.
Farroupilha, localizado na Serra Gaúcha, é o município que possui a terceira maior produção de uvas para processamento do Brasil e o maior produtor de uvas moscatéis, representando quase a metade da produção brasileira. Nos últimos dez anos, a produção e comercialização de espumantes moscatéis no Brasil aumentaram significativamente, demonstrando um crescente consumo anual. Esse produto vem conquistando diversas medalhas em concursos internacionais e agrada muito o paladar do brasileiro devido seus aromas frescos e frutados. Outro aspecto importante foi a conquista em 2015, da Indicação de Procedência de vinhos finos moscatéis Farroupilha, contribuindo ainda mais para o destaque desses produtos no mercado brasileiro e no exterior. Dentre as principais variedades cultivadas e utilizadas para a elaboração de vinhos finos tranquilos e espumantes moscatéis estão a Moscato Branco, Moscato Giallo, Moscato R2 e Malvasia de Candia. O conhecimento mais aprofundado das características sensoriais, aromáticas e qualitativas destes produtos, são importantes pois permite caracterizar o perfil dos vinhos e espumantes dessa região. O objetivo desse trabalho foi: determinar a composição aromática dos espumantes moscatéis de Farroupilha; sua evolução durante o armazenamento; caracterizar os vinhos elaborados com variedades moscatos e determinar a influência das leveduras Saccharomyces cerevisiae e Torulaspora delbrueckii na composição química e sensorial de vinhos Moscato Branco. Foram realizadas análises físico-químicas, cromatográficas e sensoriais. Os resultados permitem atribuir aos espumantes com menor tempo de armazenamento aromas cítricos e frutados e aos espumantes com maior tempo, notas de maçã, trufas, amêndoas, rosas e mel. Cada variedade de uva com a qual estes espumantes foram elaborados aportam diferentes aromas para os mesmos, contribuindo para uma grande compexidade aromática. A variedade Moscato Giallo aportou aos vinhos aromas que remetem a frutas como pera e pitanga, e ervas de quintal como alecrim. Os vinhos da variedade Moscato R2 destacaram-se pelas notas de frutas cítricas e alecrim, e os vinhos da variedade Moscato Branco apresentaram notas cítricas, pera e pitanga. As leveduras utilizadas também influenciaram na composição aromática. Os vinhos elaborados com leveduras puras de T. delbrueckii apresentaram maiores teores de acetato de isoamila (banana), hexanoato de etila (frutas, anis), 2-metil-1-propanol (alcoólico) e 2-feniletanol (rosas). Essas concentrações tendem a diminuir nas fermentações mistas. Vinhos produzidos com S. cerevisiae 100% EC 1118 se destacaram pelos maiores teores de etanal (maçã verde), 1-propanol (pungente), octanoato de etila (abacaxi, pera) e linalol (rosas). Dessa forma, este estudo demonstra que apesar da tendência do consumo de espumantes moscatéis e vinhos moscatos serem no período de 12 a 18 meses, esses produtos têm potencial para serem consumidos com maior tempo. Verificou-se também que os espumantes moscatéis de Farroupilha apresentaram uma qualidade geral equivalente aos espumantes elaborados na região de Asti, região de Denominação de Origem tradicionalmente conhecida com quase cem anos de história.
Keywords: Vinhos espumantes -Farroupilha (RS); Moscatel (Vinho) - Farroupilha (RS); Leveduras; Aromas; Sparkling wines - Farroupilha (Brazil); Muscat (Wine) - Farroupilha (Brazil); Yeast; Odors